How Fire Runs : A Novel - White, Charles Dodd, 1976- (Book collections on Project MUSE., 2020)
"A chilling, timely reminder of the moral and human costs of racial hatred. What happens when a delusional white supremacist and his army of followers decide to create a racially pure 'Little Europe' within a rural Tennessee community? As the town's residents grapple with their new reality, minor skirmishes escalate and dirty politics, scandals, and a cataclysmic chain of violence follows. In this uncanny reflection of our time, award-winning novelist Charles Dodd White asks whether Americans can save themselves from their worst impulses and considers the consequences when this salvation comes too late"--